PENGARUH DISIPLIN KERJA, PELATIHAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. SURIATAMA MITRA PERWITA MEDAN - Gilbet Saferius; Hendra Nazmi; Elisya Simalango; Veronica Veronica (Universitas Methodist Indonesia, 2020)
The purpose of this study was to analyze the effect of work discipline, training, and communication on employee performance at PT. Suriatama Mitra Perwita Medan. Researchers took the population in this study of as many as 147 employees. The number of samples in this study was 107 respondents. The sampling technique used is simple random sampling. The results showed that work discipline partially had a positive and significant effect on employee performance at PT. Suriatama Mitra Perwita Medan. Partially, the training had a positive and significant effect on employee performance at PT. Suriatama Mitra Perwita Medan. Partial communication has a positive and significant effect on employee performance at PT. Suriatama Mitra Perwita Medan. Work discipline, training, and communication simultaneously have a positive and significant effect on employee performance at PT. Suriatama Mitra Perwita Medan. positive and significant effect on employee performance at PT. Suriatama Mitra Perwita Medan. Partial communication has a positive and significant effect on employee performance at PT. Suriatama Mitra Perwita Medan. Work discipline, training and communication simultaneously have a positive and significant effect on employee performance at PT. Suriatama Mitra Perwita Medan.